Molecular evolution of LysR-type transcriptional regulation in Pseudomonas aeruginosa - Reen, F.; Barret, M.; Fargier, E.; O’Muinneacháin, M.; O'Gara, Fergal (Academic Press, 2013)
Signal perception and transduction through tightly coordinated circuits is integral to the survival and persistence of microbes in diverse ecological niches. The capacity to adapt to changes in the environment is central to their ability to thrive under adverse circumstances. Signal dependent transcriptional regulators are a key mechanism through which microbes assimilate environmental cues and mediate the appropriate adaptive response. By far the largest class of transcriptional regulator is the LysR-class, which is universally distributed among bacteria, archaea, and even eukaryotic organisms. The number of LysR-Type Transcriptional Regulators (LTTRs) varies among species with one of the largest repertoires encoded in the genome of the nosocomial pathogen Pseudomonas aeruginosa. To understand the evolutionary basis for this, we undertook to analyse the relationship between the LTTRs, both at the species and genus level. Phylogenetic analysis of the complete Pseudomonas LTTR dataset revealed significant cluster patterns based on full length and domain analysis. Interestingly, evidence of acquisition through horizontal gene transfer was rare, with divergent evolution apparently favoured. Furthermore, genes that appear to have been acquired, as well as those with a non-classical topological arrangement were clustered in distinct groups in the phylogenetic trees, indicating some ancestral association. The conservation within clusters identified in this study will provide a useful platform for future molecular analyses.